Investigating EFL Teachers' Emotional Regulation Strategies in Second Language Classroom Contexts - Kristian Florensio Wijaya (ELT Worldwide: Journal of English Language Teaching, 2021)
ABSTRACT            It is of clear importance for EFL teachers to better regulate their emotions while facing multivariate classroom vicinities offering undeniable uniqueness possessed by each learner. As a contradictory, EFL teachers frequently undergo emotional impairs during engaging in their vocation as burnout, emotional exhaustion, boredom, frustration, and reluctance. Responding to this serious teaching issue, emotional regulation strategies should be introduced earlier for EFL teachers in order to bring about positive teaching-learning influences for the whole school communities in terms of enjoyable learning activities, spirited learners, committed educators, and a solid rapport established among educational boards. This current study attempted to probe more profoundly on tangible emotional regulation strategies implemented by EFL teachers teaching in distinctive school institutions. One research problem was formulated in this study namely, what are the specific strategies EFL Teachers apply to regulate their emotions in second language learning contexts? This qualitative study utilized narrative inquiry to better obtain more obvious portrayals out of the teachers’ real-time experiences of managing their emotional states for particular teaching periods. The findings of this study displayed that the diminution of EFL teachers’ negative emotions will enable learners to achieve their gratifying learning outcomes and retain teachers to survive longer in their current vocation.